2021
DOI: 10.1101/2021.09.16.460706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Data and Collaborations at theSaccharomycesGenome Database: Updated reference genome, alleles, and the Alliance of Genome Resources

Abstract: Saccharomyces cerevisiae is used to provide fundamental understanding of eukaryotic genetics, gene product function, and cellular biological processes. Saccharomyces Genome Database (SGD) has been supporting the yeast research community since 1993, serving as its de facto hub. Over the years, SGD has maintained the genetic nomenclature, chromosome maps, and functional annotation, and developed various tools and methods for analysis and curation of a variety of emerging data types. More recently, SGD and six ot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…McClintock v2.0.0 (Nelson et al 2017) was run using default parameters. The S. cerevisiae reference genome file was downloaded from SGD (Engel et al 2022). Of the suite of tools available through McClintock we found that RelocaTE2 (Chen et al 2017) performed best against a subset of manually curated Ty insertions, so RelocaTE2 outputs were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…McClintock v2.0.0 (Nelson et al 2017) was run using default parameters. The S. cerevisiae reference genome file was downloaded from SGD (Engel et al 2022). Of the suite of tools available through McClintock we found that RelocaTE2 (Chen et al 2017) performed best against a subset of manually curated Ty insertions, so RelocaTE2 outputs were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…McClintock v2.0.0 (Nelson et al 2017) was run using default parameters. The S. cerevisiae reference genome file was downloaded from SGD (Engel et al 2022). Of the suite of tools available through…”
Section: Identification Of Ty Insertionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assist us in assessing and filtering D-SCRIPT predictions for species-specific Ophiocordyceps - Camponotus PPIs, we tested secretomes from “aspecific” fungi, which have not co-evolved with C. floridanus to establish infection and manipulation, against the C. floridanus proteome. We chose three fungi based on lifestyle, phylogeny, and availability of well-annotated genomes: C. bassiana (GenBank accession GCA_000280675.1), T. reesei (GenBank accession GCA_000167675.2), and S. cerevisiae (GenBank accession GCF_000146045.2) (Engel et al, 2022; Martinez et al, 2008; Xiao et al, 2012). We functionally annotated each fungal proteome for secreted proteins as for Ophiocordyceps (see above) and paired those secreted proteins with the Camponotus proteome for D-SCRIPT predictions (as above).…”
Section: Methodsmentioning
confidence: 99%
“…As a starting point, we collected proteins containing an MHD from three sequence databases with different levels of human expertise involved in the genome annotation process. First, the Saccharomyces Genome Database (SGD) is dedicated to the budding yeast S. cerevisiae (22) and provides comprehensive information including protein sequences from a collection of 48 S. cerevisiae strain genomes. Second, the UniProtKB/Swiss-Prot database is the expertly curated component of UniProtKB (23).…”
Section: Introductionmentioning
confidence: 99%